The need for community-led, integrated and innovative monitoring programmes when responding to the health impacts of climate change. Issue 2 (28th January 2019) - Kipp, Amy; Cunsolo, Ashlee; Gillis, Daniel; Sawatzky, Alexandra; Harper, Sherilee L.
ABSTRACT: In Northern Canada, climate change has led to many acute and interrelated health and environmental impacts experienced among Inuit populations. Community-based monitoring, in which community members participate in monitoring initiatives using various forms of technology, is a key strategy increasingly used to detect, monitor and respond to climate change impacts. To better understand the landscape of existing environmental and health monitoring programmes mobilising different technologies and operating in the North we conducted a review that used environmental scan methodologies to explore and contextualise these programmes. We consulted with academic researchers with experience in community-led monitoring, conducted systematic searches of grey and peer-reviewed literature, and conducted a secondary search for environment-health mobile-phone applications. Following specific criteria, we identified 18 monitoring programmes using information and communication technologies in the North, and three global monitoring mobile-phone applications, which cumulatively monitored 74 environment and health indicators. Several themes emerged, including the need for: (1) community leadership, (2) indicators of environment and/or human health and (3) innovative technology. This synthesis supports the development of community-led, environment-health monitoring programmes that use innovative technology to monitor and share information related to the health implications of climate change in and around Indigenous communities throughout the Circumpolar North.